1982
DOI: 10.1007/bf01816738
|View full text |Cite
|
Sign up to set email alerts
|

Adhärenz von Streptokokken der Gruppe A an Zellen des Mund-Rachen-Raumes: Lipoteicholsäure-Adhäsin und Fibronectin-Rezeptor

Abstract: The attachment of group A streptococci to oropharyngeal epithelial cells is mediated by adhesive molecules (adhesins) on the surfaces of the micro-organisms that interact with receptor molecules on the epithelial cells. The evidence that the adhesin is composed of lipoteichoic acid (LTA) complexed with bacterial cell surface proteins is as follows: (a) Among the purified cell wall substances tested, only LTA was able to inhibit attachment; (b) treatment of streptococci with anti LTA but not with antibody again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…Lipoteichoic acid was first described to be involved in streptococcal adherence to epithelial ceils and in binding to Fn [3,7,39]. However, more recent reports and our results provide evidence that fibronectin binds with a higher affinity to proteins of group A streptococci [6,11,24,31,33].…”
Section: Discussioncontrasting
confidence: 45%
“…Lipoteichoic acid was first described to be involved in streptococcal adherence to epithelial ceils and in binding to Fn [3,7,39]. However, more recent reports and our results provide evidence that fibronectin binds with a higher affinity to proteins of group A streptococci [6,11,24,31,33].…”
Section: Discussioncontrasting
confidence: 45%
“…Several different cell surface components have been implicated as fibronectin receptors on Gram-positive bacteria including lipotechioc acid (Beachey and Simpson, 1982;Courtney et al, 1986) and protein (Ryden et al, 1983). In previous studies, a fibronectin-binding protein (FNBP) with a Mr of 197-210 kd has been isolated from S. aureus strain Newman (Espersen and Clemmensen, 1982;Froman et al, 1987) and tentatively identified as a fibronectin receptor.…”
Section: Introductionmentioning
confidence: 99%
“…LTA is also important for bacterial growth since LTA can inhibit autolysin, which is critical for cell wall remodeling and necessary for replication (22). In addition, LTA is critical in pathogenesis as it is involved in bacterial adhesion to host cells (2,7,9) and initiates inflammatory cascades by activating complement (24), Tolllike receptor 2 (12,19,41), and/or CD36, a C-type lectin (21,36). In fact, a monoclonal antibody to LTA has been shown to protect animals from experimental infections (46,49,51).…”
mentioning
confidence: 99%
“…1A). The polymer would then be linked to a cytoplasmic membrane lipid anchor: Glc(␤133)AATGal(␤133)Glc(␣133)-acyl 2 Gro. The lipid anchor is critical for attaching LTA to the cytoplasmic membrane (3,13,17,30).…”
mentioning
confidence: 99%